Peningkatan Brand Image Sekolah Muhammadiyah Kota Probolinggo Melalui Penulisan Karya Ilmiah - Luayyin, Reza Hilmy; Yulina Fadilah; Robiatul Adawiyah (LPPM STAI Muhammadiyah Probolinggo, 2024)
A teacher, not just having the main activities and duties but as a teacher, also has another task that is no less important, known as a student of knowledge. Teaching is a routine activity and is normal for a teacher, but as a student of knowledge, a teacher is required to always improve his knowledge and abilities through writing a scientific paper. Writing scientific papers has several stages that must be passed, especially those used to raise the school's brand image. The Community Service Program which was carried out at the Muhammadiyah Regional Leadership propaganda building in Probolinggo City was attended by 20 participants who were teachers who taught at Muhammadiyah schools ranging from elementary schools to high schools throughout the city of Probolinggo. The method used in this service is through seminars, namely by providing knowledge through lectures, discussions and questions and answers. The results of the seminars conducted showed that there was an increase in understanding, insight, and knowledge in planning, implementing and preparing materials for writing scientific papers. To write scientific papers, a teacher really needs to do plan management, time management, and evaluation management so that they can deal with busy teaching and various other additional tasks.